Поселення раннього залізного віку біля с. Іванівка в Потясминні - Могилов, О.Д.; Руденко, С.В. (Археологія і давня історія України, 2018)
Стаття присвячена публікацій матеріалів
розвідок на поселенні раннього залізного віку біля с. Іванівка Чигиринського р-ну Черкаської обл. в басейні р. Тясмин. The article is devoted to the publication of the materials
of the settlement of the Early Iron Age near
Ivanivka in the Tyasmyn river region. Archaeological
reconnaissance here revealed the emergence of cultural
strata, represented by animal bones, ceramic moldings
and imported antique utensils, arrowheads, pins. The
materials date back to the pre-Scythian and Scythian
period: VIII—IV centuries BC.